153 Combined Exercise Echocardiography and Cardiopulmonary Exercise Testing During Pregnancy – a Longitudinal Cardiovascular Assessment in the Second Trimester. (6th June 2015) - Boardman, Henry; French, Sarah; Bradlow, William; Collins, Sally; Ioannou, Christos; Napolitano, Raffaele; Kenworthy, Yvonne; Williamson, Wilby; Cox, Peter; Lima, Eduardo; Leeson, Paul; Mackillop, Lucy
Abstract : Objectives: Cardiopulmonary exercise testing (CPET) is a well-established investigation used to stratify operative and anaesthetic risk as well as being predictive of cardiovascular morbidity and mortality. Pregnancy is a biological stress test and we hypothesised that CPET could risk stratify women with cardio-respiratory or metabolic disease during pregnancy. However, normal values in normal pregnancy are required before the predictive value of this test can be assessed in women with cardio-respiratory disease. This pilot study was designed to test the feasibility and tolerability of performing combined CPET and exercise echocardiography during pregnancy. Methods: We prospectively recruited 10 women with a singleton pregnancy; all were healthy with no known medical conditions. Each participant attended at mean 14+1 (±2 days) (visit 1) and 24+5 (±3 days) (visit 2) weeks of gestation. At each visit participants had a resting echocardiogram, fetal ultrasound scan and baseline blood sample collected. A stepwise incrementing CPET was then performed with a maternal echocardiogram at maximal exertion. A blood sample was collected at maximal exertion. Results: The participants had a mean age at visit 1 of 35 years (±4), 6 were nulliparous, BMI was 24.3 (±3.3). Combined CPET and exercise echo was successfully completed in all participants. There was no significant difference between visits for resting mean arterial pressure: 86.7 mmHg (±9.6) at visit 1 and 86.5 mmHg (±8.1) at visit 2 (p = 0.95), but resting left ventricular (LV) end diastolic volume increased from 77.3 ml (±15.1) in visit 1 to 83.8 ml (±17.2) in visit 2 (p = 0.008). Systolic function did not significantly change between visits, ejection fraction: 63.8% (±5.9) compared to 61.4% (±4.6) at visit 2 (p = 0.36). Diastolic function was not significantly altered. During the CPET test the peak workload achieved was similar at both visits: 165 Watts (±35.7) in visit 1 and 170 Watts (±36.9) in visit 2 (p = 0.51) as was VO2 max ml/Kg/min: 28.5 (±6.3) compared to 26.6 (±2.9) (p = 0.34). Respiratory exchange ratio (RER) increased significantly between visits: 1.05 (±0.05) compared to 1.11 (±0.05) at visit 2 (p = 0.01). Lactates collected increased from 1.1 mmol/L (range 0.9–1.7) before maximal exercise to 6.4 mmol/L (range 4.5–8.8) after in visit 1 (p < 0.001) and from 1.1 mmol/L (range 0.5–2.8) to 6.0 mmol/L (range 2.2–7.7) in visit 2 (p < 0.001). All participants delivered healthy live neonates at term gestation, however 1 participant developed pregnancy induced hypertension and 2 developed preeclampsia. Conclusions: We successfully demonstrated combined exercise echo and CPET studies is well tolerated in pregnant women at 14 and 24 weeks gestation. We also demonstrated this combined test as a successful technique for capturing a wealth of metabolic and cardiac structural and functional data. Cardiac volumes increased between visits. RER increased which might suggest test familiarity.